Synthesis and preliminary anticancer activity of new 1,4-dihydro-3-(3-hydroxy-2-naphthyl)-4-substituted-5H-1,2,4-triazoline-5-thiones - (:unkn) unknown (ELSEVIER SCIENCE SA, 2002)
1,4-Dihydro-3-(3-hydroxy-2-naphthyl)-4-substituted-5H-L2,4-triazolinc-5-thiones were synthesized. The structures of original eight compounds were confirmed by elemental analysis,H-1 NMR and mass spectral methods. One of the compounds (3a) was tested in vitro for its anticancer activity against 52 human tumor cell lines. (C) 2002 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: 1,2,4-triazoline-5-thione derivatives; synthesis; anticancer activity; STRUCTURE ELUCIDATION